The Role of Teachers in Increasing Reading Literacy Motivation in Islamic Cultural History Lessons at MTs Darun Nahwi Singajaya Indramayu - Didik Himmawan; Ahmad Khotibul Umam; Caniyah (Quality : Journal Of Education, Arabic And Islamic Studies, 2024)
Low student reading literacy motivation is one of the factors that causes student learning achievement to decline. This is possible because their curiosity about the subject is still low, external factors (friends, family and environment) do not support studying the subject of History of Islamic Culture and so on. Meanwhile, achievement in studying the History of Islamic Culture is influenced by several factors, for example student learning activities, the learning model used by teachers in teaching, students' ability to accept the learning provided by the teacher, students' learning motivation and so on. The role of the teacher greatly influences students' reading literacy motivation in Islamic Culture history lessons. This research use desciptive qualitative approach. The aim of this research is to find out how the teacher's role is in increasing the reading literacy motivation of MTs Darun Nahwi students and what the teacher's role is in increasing students' reading literacy motivation in the History of Islamic Culture lesson at MTs Darun Nahwi.